STRUCTURING THE PATTERN OF POWER STRUGGLE IN K.L.KAMAL'S CAMPUS: A NOVEL - Anuradha Singh (JETA (Journal of English Teaching and Applied Linguistic), 2021)
Power in itself is not a new concept; it is as older as our civilization. Power is the subject of study as its pattern is dubious. In the present day, one can easily witness a lot of power chaos in the academy's atmosphere. It demeans the institution's glory, and influences lot the learners' lives that are the future pillars of the nation. K.L.Kamal's Campus: A Novel deals with the political hegemony and exploitation scene of the academy atmosphere. The presented novel has sketched the agony of the Vice-Chancellor who has witnessed and suffered in power game despite having power in his hands. The power and ideology get a clear depiction under the observing body of the text. The presented paper will also try to analyze the concept of power and hegemony used and analyzed by the academicians. The presented paper will try to catch all the power points and roles of academia by analyzing the text in its most total form.